UPAYA MENINGKATKAN MOTIVASI DAN KEBERHASILAN BELAJAR KELISTRIKAN OTOMOTIF DENGAN MENGGUNAKAN METODE STUDENTS TEAM ACHIEVMENT DIVISION (STAD) SISWA SMK - Danang Dian Permana; Setuju Setuju (JURNAL VOKASI DEWANTARA (JVD), 2020)
The purpose of this study was to find out the motivation and learning outcome of automotive electricity andto know the students' responses to the implementation of cooperative learning types (STAD) to increasemotivation and learning achievement of automotive electrical system. This research was a classroom actionresearch (CAR). The subjects of the study were 35th grade TKR4 students at Jumo State Vocational High School.The research instruments are written tests in the form of description questions and observation sheets. Theresults showed that STAD type learning can increase learning motivation and learning outcomes. Learningmotivation in the first cycle was 54.4 with learning outcomes experiencing an increase of 70. In the second cyclelearning motivation increased to 60.23 with learning outcomes also increased to 82. In the third cycle, learningmotivation increased by 75.14 with learning outcomes also increased to 94. Based on the explanation above, itcan be concluded that the STAD learning model can increase motivation and learning outcomes of automotiveelectricity. Keywords: method, motivation, achievement